NILAI–NILAI PENDIDIKAN AKHLAK DALAM AL QUR’AN SURAT ALI IMRAN AYAT 159-160 - Nurhartanto, Armin (Profetika Jurnal Studi Islam, 2015)
The background of this research is the phenomenon of teenagers’ moral degenerate which the writer found. Considering the importance of al Qur’an for all people, it is important to implement its values as a concern especially for muslim, so the moral values in al Qur’an can be taught to the people in a good way. From this state, the writer is interested in exploring deeper about moral values in al Qur’an surah Ali Imran 159 – 160. The goals of the research are ; 1) to know the moral values in al Qur’an Surah Ali Imran 159 – 160, 2) to know how the concept of moral value in those verses, 3) to know the implication of those verses for Islamic Education in school. The research is a library research. Primier data source is al Qur’an Surah Ali Imran 159 – 160. The second data sources are book, articles or works about moral values and the implementation of moral values, considered to be true, both in sentences or content. Approaches which are used are didactic – psychology and thematic combined with qualitative analysis and are reprocessed by using deductive, inductive and comparative analysis. The result of the research show that ; 1) moral values reflected in Surah Ali Imran 159 – 160 are graceful, forgiving, solving problem by discussing it with the people, believing in Allah and believing in Allah’s help. 2) in the concept of moral education, the way Rasulullah lead his companions, he prioritizes the graceful, dissscussion, although he holds the highest authotiry. The other moral values is believing in Allah. 3) the implication of the concept of moral education according to al Qur’an Surah Ali Imran 159-160 is the concept of moral-oriented teaching.  The recommendation of this research is how the school as an education institution is able to raise moral values reflected in al Qur’an Surah Ali Imran 159-160 to the student, so they can take the lesson from the prophet’s daily life.Keywords: moral; values; implication to education.